From First Place to Last: The National Electricity Market's Policy‐Induced 'Energy Market Death Spiral'. (December 2014) - Simshauser, Paul
Abstract Microeconomic reforms that established Australia's National Electricity Market during the 1990s were extensive. State‐owned electricity commissions were vertically and horizontally restructured and many of the restructured businesses were privatised. A mandatory gross pool market was established to facilitate competition amongst generators and retailers and quickly became one of the best‐performing wholesale electricity markets in the world. Networks remain regulated under unresponsive 5‐year rate cases with flat‐rate tariffs persisting, while inflexible 'subsidy schemes' proliferated and forced generation plant entry into an already‐oversupplied market. End‐use electricity tariffs have since doubled. Misguided and overlapping policy failures are primary causes.